Neuroticism is linked to microstructural left-right asymmetry of fronto-limbic fibre tracts in adolescents with opposite effects in boys and girls. (June 2018) - Madsen, Kathrine Skak; Jernigan, Terry L.; Vestergaard, Martin; Mortensen, Erik Lykke; Baaré, William F.C.
Abstract: Neuroticism is a fundamental personality trait that reflects a tendency to experience heightened negative affect and susceptibility to stress. Negative emotionality has been associated with fronto-limbic brain structures and connecting fibre tracts. The major fibre tracts connecting the frontal and limbic brain regions are the cingulum bundle and uncinate fasciculus. We previously found that healthy adults with higher neuroticism scores had decreased left relative to right fractional anisotropy (FA) of the cingulum. Both cingulum and uncinate fasciculus FA increases throughout childhood and into early adulthood. Since adolescence is associated with an increased incidence of anxiety and mood disorders, for which neuroticism is a known risk factor, the question arises whether the association between neuroticism and fronto-limbic white matter microstructure asymmetry is already present in children and adolescents or whether such relationship emerges during this age period. To address this question, we assessed 72 typically-developing 10-to-15 year-olds with diffusion-weighted imaging on a 3 T magnetic resonance scanner. Neuroticism was assessed with the Junior Eysenck Personality Questionnaire. FA and parallel and perpendicular diffusivity measures were extracted for cingulum, uncinate fasciculus as well as the white matter underlying the ventromedial prefrontal cortex. Higher neuroticism scores were associated with decreased left relative to right cingulum FA in boys, while in girls, higher neuroticism scores were associated with increased left relative to right cingulum and ventromedial prefrontal white matter FA, indicating that there are sex differences in the neural correlates of neuroticism. Our findings suggest that the link between neuroticism and frontal-limbic white matter microstructure asymmetry likely predates early adolescence. Future studies need to elucidate the significance of the observed sex differences in the neural correlates of neuroticism. Highlights: We examined the link between neuroticism and fronto-limbic white matter asymmetry. Neuroticism showed a sex-specific relationship with cingulum FA asymmetry. In boys, neuroticism was linked to decreased left relative to right cingulum FA. In girls, neuroticism was linked to increased left-to-right cingulum FA. The neurobiological significance of these sex differences needs to be elucidated.